Monitoring of Human Development in Regions of Ukraine (Integrated Approach) - Stolyarova, V.; Shynkaryuk, O.; Stolyarov, V.; Antoshkin, V.; Goryacha, O.; Frolova, G. (Економічний вісник Донбасу, 2021)
The article summarizes the basics of information and methodological metrology of regional human development, the formation and development of which were approved by the Government of Ukraine in 2001, 2012 and 2017. Particular attention is paid to the problems of coordination of the assessment of the dynamics of the components of the Regional Human Development Index (RHDI) with the indicators of the National Regional Development Strategies for the periods up to 2015, 2020 and 2027.
In the context of assessing the effectiveness and efficiency of the mechanism of state regulation of regional human development on the basis of its forecasting revealed the essence and content of the 4 stages of the algorithm of comprehensive rating assessment of RHDI. Methods of clustering of regions by appropriate components, methods and procedures of composition and decomposition of components of RHDI were used in order to ensure socio-economic security of regions.
Differentiation of the system of indicators and procedures for monitoring regional human development at the subnational (regional) level allows to more objectively determine the socio-economic policy of regional and local executive bodies to improve the quality of life of villages, towns, cities, districts and administrative regions of Ukraine. У статті узагальнено основи інформаційно-методичної метрології регіонального людського розвитку, становлення та розвиток яких затверджувались Урядом України у 2001, 2012 і 2017 роках. Особливу увагу зосереджено на проблемах узгодженості оцінки динаміки складових Індексу регіонального людського розвитку (ІРЛР) з показниками Державних стратегій регіонального розвитку на періоди до 2015, 2020 і 2027 років.
У контексті оцінки результативності і ефективності механізму державного регулювання регіонального людського розвитку на основі його прогнозування розкриті сутність і зміст чотирьох етапів алгоритму комплексної рейтингової оцінки ІРЛР. Використано методи кластеризації регіонів за відповідними компонентами, прийоми і процедури композиції та декомпозиції складових ІРЛР з метою забезпечення соціально-економічної безпеки регіонів.
Диференціація системи показників і процедур моніторингу регіонального людського розвитку на субнаціональному (обласному) рівні дозволяє більш об’єктивно визначити соціально-економічну політику регіональних і місцевих органів виконавчої влади щодо підвищення якості життя населення сіл, селищ, міст, районів та адміністративних областей України загалом. В статье обобщены основы информационно-методической метрологии регионального человеческого развития, становление и развитие которых утверждались Правительством Украины в 2001, 2012 и 2017 годах.
Особое внимание было уделено проблемам согласованности оценки динамики составляющих Индекса регионального человеческого развития (ИРЧР) с показателями Государственных стратегий регионального развития на периоды до 2015, 2020 и 2027 годов.
В контексте оценки результативности и эффективности механизма государственного регулирования регионального человеческого развития на основе его прогнозирования раскрыты сущность и содержание четырех этапов алгоритма комплексной рейтинговой оценки ИРЧР. Были использованы методы кластеризации регионов по соответствующим компонентам, приемы и процедуры композиции и декомпозиции составляющих ИРЧР с целью обеспечения социально-экономической безопасности регионов.
Дифференциация системы показателей и процедур мониторинга регионального человеческого развития на субнациональном (областном) уровне позволяет более объективно определить социально-экономическую политику региональных и местных органов исполнительной власти по повышению качества жизни населения сел, поселков, городов, районов и административных областей Украины в целом.